THE INTEGRAL ROLE OF MOTIVATION, DISCIPLINE, AND WORK ENVIRONMENT IN IMPROVING EMPLOYEE PERFORMANCE IN SURABAYA PLANTATIONS - Hidayati, Levina Zahirah; Firdaus, Vera; Sumartik, Sumartik (International Journal of Business, Law and Political Science, 2024)
General Background: Human Resources (HR) significantly impact organizational performance, influencing overall productivity and success. Specific Background: This study investigates the effect of work motivation, work discipline, and work environment on employee performance at PT Kebun Sayur Surabaya. Existing literature suggests that while HR development is crucial, specific factors influencing employee performance remain underexplored. Knowledge Gap: Previous research has often overlooked the combined effects of these factors on performance, particularly in the context of Indonesian companies. Aims: This study aims to provide a comprehensive analysis of how work motivation, work discipline, and work environment impact employee performance at PT Kebun Sayur Surabaya. Results: Utilizing quantitative methods and SmartPLS 3.2.8, the study finds that work motivation, work discipline, and work environment each have a significant positive effect on employee performance. The study highlights that employees’ performance improves with enhanced motivation, strict discipline, and a supportive work environment. Novelty: The study’s novelty lies in its integrated approach, using total sampling of all employees to analyze these three variables collectively in a specific organizational context. Implications: The findings suggest that PT Kebun Sayur Surabaya should focus on strengthening work motivation, reinforcing discipline, and improving the work environment to boost employee performance. Implementing effective HR strategies based on these factors can drive organizational growth and success.